Direct and inverse theorems for Bernstein polynomials with inner singularities - Wen-ming Lu; Lin Zhang (Journal of the Egyptian Mathematical Society, 2012)
We introduce a new type of Bernstein polynomials, which can be used to approximate the functions with inner singularities. The direct and inverse results of the weighted approximation of this new type of combinations are obtained.